2022
DOI: 10.1371/journal.pgen.1010086
|View full text |Cite
|
Sign up to set email alerts
|

High sorbic acid resistance of Penicillium roqueforti is mediated by the SORBUS gene cluster

Abstract: Penicillium roqueforti is a major food-spoilage fungus known for its high resistance to the food preservative sorbic acid. Here, we demonstrate that the minimum inhibitory concentration of undissociated sorbic acid (MICu) ranges between 4.2 and 21.2 mM when 34 P. roqueforti strains were grown on malt extract broth. A genome-wide association study revealed that the six most resistant strains contained the 180 kbp gene cluster SORBUS, which was absent in the other 28 strains. In addition, a SNP analysis revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Fungi can be exposed to various chemical biocides, in particular in crops and in food with preservatives. in some strains isolated from spoiled food, which has been attributed to the presence of a horizontally transferred region named SORBUS (Punt et al 2022). Here, we studied the impact, on the growth of the different P. roqueforti populations, of chemical preservatives used in the food industry (natamycin and sorbate), a fungicide used for crop treatment (tebuconazole) and of a weak organic acid present in cheese (lactic acid resulting from lactose degradation by lactic acid bacteria).…”
Section: Specific Traits In Penicillium Roqueforti Populations Benefi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi can be exposed to various chemical biocides, in particular in crops and in food with preservatives. in some strains isolated from spoiled food, which has been attributed to the presence of a horizontally transferred region named SORBUS (Punt et al 2022). Here, we studied the impact, on the growth of the different P. roqueforti populations, of chemical preservatives used in the food industry (natamycin and sorbate), a fungicide used for crop treatment (tebuconazole) and of a weak organic acid present in cheese (lactic acid resulting from lactose degradation by lactic acid bacteria).…”
Section: Specific Traits In Penicillium Roqueforti Populations Benefi...mentioning
confidence: 99%
“…potassium sorbate and natamycin). In P. roqueforti , sorbate resistance has been reported in some strains isolated from spoiled food, which has been attributed to the presence of a horizontally transferred region named SORBUS (Punt et al 2022). In addition, the P. roqueforti population associated with silage may be exposed to triazoles, commonly used as fungicides on crops.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative genomics and transcriptomics in this study focussed on conidial heat resistance, and thus the presence of homologous weak acid resistance genes was not studied. Recently, the same GWAS methods were used to identify weak acid resistance gene cluster SORBUS in P. roqueforti (Punt et al, 2022b). For every P. variotii strain used in this study, a higher MIC for sorbic acid was found than previously reported for a P. variotii strain isolated from a South American soft drink production facility (Stratford et al, 2009).…”
Section: Discussionmentioning
confidence: 47%
“…Besides the eight P. variotii strains containing the 60 kbp cluster, the cluster was identified in nine of the 21 P. chrysogenum assemblies currently available on NCBI (https://www. ncbi.nlm.nih.gov/assembly/?term=penicillium+chrysogenum, June 21, 2021) and in one out of 34 newly sequenced P. roqueforti genomes (Punt et al, 2022b). In addition, various Aspergillus species contain fragments of the 60 kbp cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation